Avaliação da técnica BIPAP no auxílio ao diagnóstico da doença coronariana - Aumann, Sonia Maria (2005)
The ergometric test is one of the most important medical examinations in order to diagnose coronary disease. However, it shows a great limitation, because individuals get tired even before they have reached a predefined cardiac frequency (CF). In the developed research, it is proposed the application of BiPAP technique during the ergometric test as a means of prolonging the period of testing and improving its performance for the coronary disease diagnostic. As a volunteer adaptation to the breathing booster device, the 12 min walking test before the ergometric one was performed. A group of 31 male coronary patients, 50 up to 68 years old, participated of the walking test and 30 patients, of the ergometric one. The volunteers were submitted to an experimental protocol consisted of 2 stages: in the first one, without the breathing booster device, and in the second one, using it. For the 12 min walking test, it was compared the variations of the coursed distance and the cardiac frequency achieved between the 2 stages. Along the ergometric test, it was measured and compared the cardio-respiratory parameters: arterial pressure, cardiac frequency, metabolic equivalent, double product, oxygen consumption, oxygen saturation and lactic acid. With the application of the clinical protocol, we tried to reach the maximum cardiac frequency (CFM), and to provoke the appearing of late exhaustion and fatigue, which influence the coronary disease diagnostic. For the ergometric test, using the BiPAP technique, the results had shown volunteers wickedly physical performance, reaching no CFM and moreover initiating the process of breathing fatigue precociously. On the walk test, with moderated effort, the volunteers overcame the walked distance in relation to the walking without the use of the breathing booster device, indicating, on this way, that the BiPAP technique can promote an increase of the distance and of FC. For the ergometric test, however, we concluded that the BiPAP technique does not increase metabolic and physiologic parameters which can improve the sensitivity and precision of the coronary disease diagnostic, considering that it had produced a reduction of breathing work and oxygen saturation, bringing to dyspnea and to respiratory fatigue precociously, respectively.